Blanching treatment effect on the enzymatic activity of polyphenoloxidase in two varieties of sweet potato (Ipomoea batatas Lam.) (2016)
The effect of scalding time and temperature on the enzyme activity of polyphenol oxidase in two varieties of sweet potatoes (white and red) was studied with the aim of obtaining and evaluating the behavior of this enzyme. The samples were subjected to scalding temperatures (75, 80 and 85°C) and times of 30, 60, 90, 120, 150, 180 s in distilled water containing 0.5% citric acid and 1% ascorbic acid, regulating the pH and controlling the oxidation. In the evaluation of the temperature effect, the activity of the enzyme polyphenol oxidase in the red variety was initially ∆UAbs 0.263 min-1 mg-1 protein (variation of absorbance units per minute per gram of protein), which decreased to 0.0347 ∆UAbs min-1 mg-1 protein at the temperature of 85°C and 180 s. The white variety had a value of ∆UAbs 0.128 min-1 mg-1 protein, which decreased to values of ∆UAbs 0.0177 min-1 mg-1 protein at the same temperature and time. It was concluded that the activity of the enzyme polyphenol oxidase decreased by 86.8% in the red variety and 86.2% in the white variety through the blanching action.